Movements in art since 1945 : issues and concepts / Edward Lucie-Smith. - Lucie-Smith, Edward. (World of art., 1995)
A clear, swift-moving account of the visual arts in the past half century. All the most recent trends and artists are discussed including Minimal and Conceptual art, Arte Povera, the influence of Joseph Beuys, Neo-Expressionism, Neo-Conceptualism and the work of Feminist and Gay artists as aspects of Postmodernism. The emergence of the powerful work - until recently considered 'peripheral' - of African-American and regional American artists, and new trends in Latin American, Russian, Japanese, Chinese, Korean, modern African, Caribbean and Aboriginal art are all introduced and discussed, providing a world panorama of art at the end of the century. A full bibliography and for the first time comprehensive chronologies of key events from 1940 to the present make this book a unique guide to the main issues, concepts and players.